Systemic lupus erythematosus, Sjögren's syndrome and glomerular nephritis. Issue 616 (February 1977) - Sobel, J. D.; Talor, Z.; Alroy, G.; Lichtig, C.; Valero, A.
Abstract : The combination of systemic lupus erythematosus, Sjögren's disease and severe diffuse glomerular nephritis has only rarely been reported. A 14-year-old girl is described with lupus nephritis in whom co-existent clinical and histological features of Sjögren's syndrome were found. These include bilateral parotid enlargement, xerostomia, increased serum amylase, reduced salivary secretion and lymphocyte infiltration of both salivary glands and kidneys. The co-existence of systemic lupus erythematosus with Sjögren's syndrome is discussed together with a consideration of pathogenesis.